Black male teachers diversifying the United States' teacher workforce - Lewis, Chance W. 1972-; Toldson, Achebe, 1973- (Advances in race and ethnicity in education,, 2013)
Recently, U.S. Secretary of Education Arne Duncan suggested that placing Black men in the classroom as teachers is a critical need in the American educational system. Many education policymakers and researchers falsely believe that Black male teachers have a primary responsibility to foster the social development of Black male students. However, increasing the presence of Black male teachers improves the diversity of the profession and should be viewed as a benefit to the system, as they provide quality services to all students regardless of race and/or gender. This edited volume offers sound suggestions for advancing diversity in the teaching profession. It provides teacher education programs with needed training materials to accommodate Black male students, and school district administrators and leaders with information to help recruit and retain Black male teachers. Each chapter will feature policy and practice recommendations and a case example to spur action and increase opportunities for discussion.